An examination of the cognitive construction of fit among chief executives and senior elected members in Local Authorities in England and Wales: is it gendered? - Nelson, Dale (Cranfield University, 2004)
This research examines the cognitive construction of ‘Fit’ among male and female Chief Executives and Elected Members in Local Government. Using repertory grid technique, constructions of ‘Fit’ were elicited from 20 male and female Chief Executive and 20 male and female Elected Member pairs in England and Wales. Using a ‘grounded theory’ approach to content analysis, constructs were categorised into 16 categories. Results showed that the construction of ‘Fit’, among both Chief Executives and Elected Members contains elements of both P-J and P-O fit. Both Chief Executives’ and Elected Members’ notions of ‘Fit’ have some overlap with United Kingdom, public sector based constructs of Transformational Leadership. However, Elected Members’ construction of ‘Fit’ is qualitatively different, from that described by the Chief Executives in the sample. Male Elected Members lacked the relational and communal constructs expected in Transformational models. When the total sample was analysed by sex, male and female respondents also showed differences in their constructions of ‘Fit’. Males and females placed emphases on different sub-components of ‘Fit’ and these sex differences, although subdued, are broadly in line with previous repertory grid studies outlining perceived differences between male’s and female’s management and leadership styles. As a result it is concluded that ‘Fit’ is a gendered construct. This has important implications for (1) who is being appointed to senior positions in local government; (2) the assessment of leadership in more general terms; (3) the need for effective and close working relationships between Chief Executive and Leader of the Council; (4) the progress of the centrally driven modernising agenda in local government; and finally (5) the likelihood of significant culture change in local government in the near future.